Blood urea nitrogen - independent marker of mortality in sepsis - Harazim, Martin; Tan, Kaiquan; Nalos, Marek; Matejovic, Martin (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
BACKGROUND: This retrospective study examines the relationship between admission Blood Urea Nitrogen (BUN) levels and clinical outcomes in patients with sepsis from two separate cohorts in the Czech Republic and the United States. METHODS: The study included 9126 patients with sepsis between January 2014 and December 2018. Kaplan-Meier survival curves and Cox regression were used to analyse the data. An optimal cut-off was calculated by means of the Youden-Index. RESULTS: BUN at ICU admission was categorized as 10-20, 20-40 and >40 mg/dL. Comparing the group with the highest BUN levels to the one with lowest levels, we found HR for 28 days mortality 2.764 (CI 95% 2.37-3.20; P<0.001). We derived an optimal cut-off for prediction of 28 days mortality of 23 mg/dL. The association between BUN and 28 days mortality remained significant after adjusting for potential confounders - for APACHE IV (HR 1.374; 95%CI 1.20-1.58; P<0.001), SAPS2 (HR 1.545; 95%CI 1.35-1.77; P<0.001), eGFR (HR 1.851; 95%CI 1.59-2.16; P<0.001) and several other variables in an integrative model. CONCLUSIONS: Our findings support the BUN level as an independent and easily available predictor of 28 days mortality in septic critically ill patients admitted to an ICU.
Keywords: Blood Urea Nitrogen; APACHE; dusík močoviny v krvi; BUN; retrospektivní studie; Intensive Care Units; sepse; big data; Humans; urea; mortality; jednotky intenzivní péče; lidé; Retrospective Studies; sepsis; Sepsis; Prognosis; prognóza